Analisis Kesulitan Belajar Kosakata Bahasa Inggris pada Siswa Kelas II SD Negeri Duren Temanggung - Anggita Lia Anggraini; Muhammad Arief Budiman; Lina Putriyanti (STKIP Andi Matappa Pangkep, 2023)
This study has two objectives namely to identify and describe the factors that influence the difficulty of learning English vocabulary in grade II students at SD Negeri Duren Temanggung Regency and to identify and describe solutions to overcome difficulties in learning English vocabulary in grade II students. This type of research is descriptive qualitative. The research subjects were class II students. Data collection techniques using observation, interviews, questionnaires, documentation and tests. Data analysis procedures used the Miles & Huberman interactive model technique (data reduction, data presentation and conclusion). The results of the study showed that there were still many students having difficulty learning English vocabulary in writing and vocabulary mastery from 19 students as many as 12 students had difficulty especially in writing (writing) and vocabulary mastery. Two factors that cause students to have difficulty learning English vocabulary are internal factors and external factors. The conclusion of this study is that there are several factors that influence students' difficulties in learning English vocabulary material. These factors are internal factors and external factors.